Diagnostic Value of Ultrasound Elastography in the Differentiation of Breast Invasive Ductal Carcinoma and Ductal Carcinoma In situ - Shi, Jian; Chen, Luzeng; Wang, Bin; Zhang, Hong; Xu, Ling; Ye, Jingming; Liu, Yinhua; Shao, Yuhong; Sun, Xiuming; Zou, Yinghua (Current medical imaging reviews, 2023)
Ultrasound elastography (US-E) has been shown superior to the conventional US in diagnosing benign and malignant breast lesions. In contrast, the role of US-E in the differentiation of breast invasive ductal carcinoma (IDC) and ductal carcinoma in situ (DCIS) has been poorly described. This study was designed to examine the diagnostic value of US-E in the differentiation of IDC and DCIS. Medical records of all patients who underwent preoperative US-E evaluation and were diagnosed with IDC or DCIS at our hospital from April-December 2019 were retrieved and analyzed. Those who had prior surgical treatment, chemotherapy or radiotherapy were excluded. Twenty women with DCIS and 111 women with IDC were included in this study. There were no significant differences in age, maximum lesion diameter and tumor volume between the two groups. While shear wave velocity (SWV) inside the lesion and in the surrounding tissue, strain ratio and tumor area ratio were not substantially different between the two groups, SWV at the edge of the lesion was significantly higher in IDC cases, which had an AUC value of 0.66 with a sensitivity of 65.8% and a specificity of 60.0% for the differential diagnosis of IDC and DCIS. Edge SWV is significantly higher in IDC than that in DCIS, which had a moderate diagnostic value for the differentiation of IDC and DCIS, similar to the performance of diffusion-weighted magnetic resonance imaging as reported in the literature. In terms of cost-effectiveness, US-E could be very useful while waiting for further evaluations to determine whether US-E combined with other diagnostic modalities improves the diagnostic performance.